Isolation and Characterization of Diesel Oil-Degrading Pseudomonas aeruginosa - Mallu, Maheswara Reddy (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: Diesel oil-degrading bacterium Pseudomonas aeruginosa was isolated from diesel oilpolluted soil sample from various locations of diesel loco sheds, Vijayawada City, Andhra Pradesh, India. Materials and Methods: Two different strains having specific ability to degrade and utilize diesel oil for their growth were isolated. The isolated bacterium was identified as P. aeruginosa based on its 16S rRNA typing as well as various morphological and physiological characteristics. Results: On the basis of molecular analysis, these strains were belonged to genus Acinetobacter. Antibiotic sensitivity of the isolates was also checked against different antibiotics of which they showed resistance against amoxicillin, levofloxacin, minocycline, chloramphenicol, and sulfadiazine. Conclusion: This study might be an important step toward the bioremediation of diesel oil contaminated soil and waste water.